2010
DOI: 10.1080/24748668.2010.11868519
|View full text |Cite
|
Sign up to set email alerts
|

Video analysis of tackles in professional rugby league matches by player position, tackle height and tackle location

Abstract: Special thanks to David Perry for access to the Sports Performer video analysis software used for this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
44
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 18 publications
2
44
0
1
Order By: Relevance
“…Of the 6 coded plays or situations in which the CIR was used, the hitup (82 % of cases) was the only play that accounted for more than 10 % of the CIR use. Previous studies have shown that forwards are involved in tackles more frequently than other playing positions [3,15]. Both of these findings were also consistent with the prior video analysis of NRL players [7].…”
Section: Inter-rater Reliability (Irr)supporting
confidence: 89%
See 2 more Smart Citations
“…Of the 6 coded plays or situations in which the CIR was used, the hitup (82 % of cases) was the only play that accounted for more than 10 % of the CIR use. Previous studies have shown that forwards are involved in tackles more frequently than other playing positions [3,15]. Both of these findings were also consistent with the prior video analysis of NRL players [7].…”
Section: Inter-rater Reliability (Irr)supporting
confidence: 89%
“…Therefore, a third rater was used to facilitate a consensus decision for the frequency calculations in 14 cases. frequency of tackles each playing position was involved in) [3,4,15]. Of the 6 coded plays or situations in which the CIR was used, the hitup (82 % of cases) was the only play that accounted for more than 10 % of the CIR use.…”
Section: Inter-rater Reliability (Irr)mentioning
confidence: 99%
See 1 more Smart Citation
“…walking, jogging) [3]. As a result of these activities, participants often experience between 29 and 74 physical collisions (tackles and ball-carries) per game [4,5]. These collisions carry an inherent risk of injury, including concussion [1], as impacts to the body and head occur frequently [6].…”
Section: Introductionmentioning
confidence: 99%
“…2 As a result of these activities, players can experience 29 to 74 physical collisions (tackles and ball-carries) per game. 3,4 From these physical collisions there is an inherent risk of injury , including concussion 5 to the players involved, as impacts to the body and head happen. 1 A pooled analysis of rugby league concussions 6 reported an incidence of 7.7 per 1000 match hours.…”
Section: Introductionmentioning
confidence: 99%